Optimum dose of neostigmine to reverse shallow neuromuscular blockade with rocuronium and cisatracurium. (13th February 2016) - Choi, E. S.; Oh, A. Y.; Seo, K. S.; Hwang, J. W.; Ryu, J. H.; Koo, B. W.; Kim, B. G.
Summary: We examined the use of neostigmine for reversing shallow (defined as train‐of‐four ratio of 0.5), cisatracurium‐ and rocuronium‐induced neuromuscular block in 112 patients, by use of 0 μg.kg −1, 10 μg.kg −1, 20 μg.kg −1 or 40 μg.kg −1 dose of neostigmine for reversal. The times from neostigmine administration to train‐of‐four ratios of 0.7, 0.9 and 1.0 were evaluated. Analysis of variance showed that the duration of action was significantly longer after cisatracurium compared with rocuronium. The time to reach a train‐of‐four ratio of 1.0 was significantly shorter with neostigmine 40 μg.kg −1 compared with lower neostigmine doses, and at this dose the time did not differ between cisatracurium and rocuronium. The recovery time from a train‐of‐four ratio of 0.5–1.0 did not differ between cisatracurium and rocuronium, and was significantly shortened by the administration of neostigmine. We conclude that a neostigmine dose of 40 μg.kg −1 was the most effective at reducing recovery time after neuromuscular blockade.